Robustness assessment of a novel IMRT planning method for lung radiotherapy. Issue 6 (June 2016) - Ahanj, Mohsen; Bissonnette, Jean-Pierre; Heath, Emily; McCann, Claire
Highlights: BV plans were robust to variations in the time spent at each respiratory phase. ITV and BV plans were not robust to a 3 mm increase in respiratory motion amplitude. Increased boost height had negligible improvement of tumour coverage of BV plans. To improve robustness of BV, the width of the boost volume needs to be increased. Abstract : Purpose: Conventional radiotherapy treatment planning for lung cancer accounts for tumour motion by increasing the beam apertures. We recently developed an IMRT planning strategy which uses reduced beam apertures in combination with an edge enhancing boost to compensate for loss of coverage due to respiration. Previous results showed that this approach ensures target coverage while reducing lung dose. The current study evaluated the robustness of this boost volume (BV) technique to changes in respiratory motion, including amplitude and time spent in each respiratory phase. Methods: ITV and BV plans were generated for one NSCLC patient with respiratory motion amplitude of 0.9 cm. Dose was accumulated for three different weightings of the 4DCT phases. Nine numerical phantoms were created with tumour sizes of 3 cm, 5 cm and 6.5 cm and motion amplitudes of 7 mm, 10 mm and 14 mm. The robustness of BV and ITV plans to variations in motion amplitude was assessed. The relative contributions of the width of the boost volume and the boost dose to plans efficacy and robustness were investigated. Results: The BV plans were robust to typical variations in the time spent at each respiratory phase. Both ITV and BV plans were robust to 3 mm amplitude decreases but not to 3 mm amplitude increases. Increasing the boost dose from 110% to 120% of the prescription dose had negligible effect in improving tumour coverage. Conclusion: To improve the robustness of this technique the width of the boost volume needs to be increased.